17세기 국어의 ㅔ>ㅐ 모음 하강에 대하여 - 여은지(Yeo, Eunji) (열린정신 인문학 연구, 20(3), 2019)
본고에서는 17세기 국어에서 발생한 ㅔ>ㅐ 변화의 분포 양상을 검토하고, 해당 변화의 음운론적 성격에 대하여 논의하였다. 그 결과 ㅔ>ㅐ 변화가 /e/, /ɛ/ 단순모음화가 발생하기 전 국어 모음 체계 재조정 과정에서나타난 모음 하강의 일종이었음을 밝혔다. ㅔ>ㅐ의 변화는 주로 비어두 위치에서, 선행 자음이 연구개음일 때 나타났다. 16-17세기 사이에 발생한ㅔ~ㅐ의 혼기는 /əj/~/aj/의 혼란을 반영한 표기이며, 이후 이들 모음의단순모음화가 이루어지면서 /e/~/ɛ/의 합류로 이어졌다고 파악하였다. ㆍ 의 제1 단계 변화로 인하여 비어두 위치에서 ㆍ가 ㅡ와 중화됨으로써 비어두의 ㅓ가 후설 모음으로서의 변이음을 가지게 되었고, 이로 인해 비어두의 /ㅓ/와 /ㅏ/의 거리가 가까워진 결과 두 모음의 혼동이 발생한 것이다. ㅓ~ㅏ의 음성적 혼란으로 인해 [əj]~[aj]의 혼란이 일부 어사에서 [e]>[ɛ] 의 변화로 이어졌고, 이후 ㅔ, ㅐ의 단순모음화가 발생하면서 현재의 /e/>/ ɛ/의 모습으로 남았다. This article has reviewed the trend of distribution of the changes in ㅔ>ㅐ that was risen in the Korean language in the 17th century and discussed for the phonological characteristics of the applicable change. As a result, the change of ㅔ>ㅐ was shown to be a type of vowel falling that appeared in the process of readjusting the vowel system of the Korean language prior to have a monophthongization of /e/, /ɛ/. The change of ㅔ>ㅐ was mainly appeared in the wordinternal position with the previous consonant to be the soft palatal consonant. The mixed indication of ㅔ~ㅐ occurring inbetween 16th and 17th century is the indication that reflected the confusion of /əj/~/aj/, and with the monophthongization of these diphthongs established, it was made by merging /e/~/ɛ/. Due to the phase 1 change of ㆍ, ㆍ and ㅡ were neutralized at the word－internal position to change the varied sound as with ㅓ of word－internal position as the back tongue vowel, and because of this, the confusion of the two vowels occurred as a result of the distance between /ㅓ/ and /ㅏ/ of the word－internal position getting closer. Due to the negative confusion of ㅓ~ㅏ, the confusion of [əj]~[aj] led to the change of [e]>[ɛ] in some of the terms, and thereafter, the monophthongization of ㅔ and ㅐ occurred to remain as the appearance of present /e/>/ɛ/. KCI Citation Count: 0